Repression, Neurosis and Anxiety: The Triad of Psychic Alienation in Eugene O’Neill’s Strange Interlude - Aldhafeeri, Hilalah (Dirasat: Human and Social Sciences, 2021)
This paper attempts to explore repression, neurosis and anxiety as unconscious stimuli of behavioral alienation in Eugene O’Neill’s Strange Interlude. It concentrates on the fragmentation of the American society by dint of depicting disillusion and disappointment embedded in the family disintegration. Another gap which the study attempts to fill is the application of Sigmund Freud’s concepts of repression, neurosis and anxiety. They will be utilized to discover the influence of the unconscious mind as an impetus of the characters’ alienation. The characters unconsciously repress their negative experiences. When such experiences are triggered, the characters become neurotic. Therefore, neurosis will be argued as a transitional psychic phase which shapes conscious anxiety. As such, this study, through using Freud’s arguments, will identify anxiety as the final abnormal behavioral phase of the characters’ psychic alienation. Thus, the characters’ alienated behaviors are ultimately formed by accumulation of repressed erotic desires depicted in the play.